Late recurrence of a papillary thyroid carcinoma 37 years after hemithyroidectomy: Solitary, left cervical lymph node metastasis evident on fluorodeoxyglucose positron-emission tomography/computed tomography images revealing nodular uptake - Kunogi, Hiroaki; Naoi, Yutaka; Matsumoto, Toshiharu; Ozaki, Yutaka (World Journal of Nuclear Medicine, 2020)
In patients with well-differentiated papillary thyroid carcinoma (PTC), late recurrence is very rare. It is unusual that 18F-fluorodeoxyglucose positron-emission tomography/computed tomography (PET/CT) shows hypermetabolic lesions in patients with well-differentiated PTC metastases. We demonstrate an exceptional case exhibiting a first relapse 37 years after hemithyroidectomy to treat PTC. Recurrent metastasis of a PTC should be considered as a differential diagnosis even if the elapsed time from the initial treatment is great. A left cervical lymphadenopathy, which exceptionally exhibited a hypermetabolic lesion on PET/CT, should be considered a metastatically well-differentiated PTC.
Keywords: Late recurrence; papillary thyroid carcinoma; positron-emission tomography/computed tomography